Perkembangan sastra Arab dan teori sastra Islam - Manshur, Fadlil Munawwar, 1960-; Marsono, Dr. (Yogyakarta, Indonesia : Pustaka Pelajar, 2011)
Development of Arabic and Islamic literary works.
Includes bibliographical references (pages 181-191) and index.
Keywords: Arabic literature -- History and criticism; Islamic literature -- History and criticism; Malay literature -- Arab influences; Malay literature -- Islamic influences